EFEKTIVITAS PENGALOKASIAN DANA DESA DALAM MENDUKUNG PEMERATAAN EKONOMI DESA (Studi Di Desa Uma Beringin Kecamatan Unter Iwes) - Nirmala, Alda Dwi; Azzahra, Fatimah; Al-Faqih, Zalwan (Jurnal Ekonomi & Bisnis, 2025)
Village Funds are central government aid funds sourced from the State Budget (APBN) allocated for villages. Village Fund Allocation is directed to support the implementation of village governance, infrastructure development, and community empowerment to create more independent, prosperous, resilient, and sustainable villages, as well as reducing disparities and equitable development. However, in practice, the effective use of Village Funds still faces various obstacles, resulting in suboptimal development outcomes and community expectations. Therefore, this study aims to analyze the effectiveness of Village Fund allocation in economic equity in Uma Beringin Village, Unter Iwes Sub-District, Sumbawa District. This research used a descriptive method with a qualitative approach. Data collection was conducted using direct observation, in-depth interview, and documentation. The research subjects were the Village Government and the community of Uma Beringin Village, Unter Iwes Sub-District. The data analysis techniques used include thematic analysis to find patterns and themes from field data, as well as comparative analysis to compare views between the village government and the community. The results of this study showed that although the fund allocation mechanism is in place, community involvement in planning and supervision remains uneven. The dominance of certain groups and lack of transparency restrict citizen participation, especially among marginalized groups. However, involving local labor in infrastructure development empowers residents and enhances local economic circulation. The results suggest that Village Fund allocation needs to be accompanied by increased community participation and management transparency to achieve more equitable economic benefits for the village.